The Purpose of Teaching the Basic Features of Pharmaceutical Information to Students of Medical Universities - Berdievna, Abdullaeva Sanobar; Husniddinovna, Abdullaeva Raykhona; Komiljonovna, Khudaynazarova Nozima (American Journal of Biomedicine and Pharmacy, 2025)
In addition to the skills of quick search of pharmaceutical information, the ability to analyze, summarize and present information to patients and other health care professionals is of great importance for a pharmacist. Practical work allows you to bring theory as close as possible to the practice of pharmaceutical activities. This article discusses the importance of obtaining, processing and using pharmaceutical information and teaching students of medical universities the main features of pharmaceutical information The information is covered and this helps students gain in-depth practical skills.